Serosurveillance of Coxiellosis (Q-fever) and Brucellosis in goats in selected provinces of Lao People's Democratic Republic. - Rebekah J L Burns; Bounlom Douangngeun; Watthana Theppangna; Syseng Khounsy; Mavuto Mukaka; Paul W Selleck; Eric Hansson; Matthew D Wegner; Peter A Windsor; Stuart D Blacksell (Public Library of Science (PLoS), 2018)
Goat raising is a growing industry in Lao People's Democratic Republic, with minimal disease investigation to date, especially zoonoses. This study determined the proportional seropositivity of two zoonotic diseases: Q fever (causative agent Coxiella burnetii) and Brucellosis (Brucella species) in goats across five provinces (Vientiane Capital, Xayaboury, Xiengkhuang, Savannakhet and Attapeu). A total of 1458 goat serum samples were tested using commercial indirect ELISA for both pathogens, plus Rose Bengal agglutination test for Brucellosis. Overall individual seropositivity of C. burnetii was 4.1% and Brucella spp. was 1.4%. A multiple logistic regression model identified that province (Vientiane Capital, p = 0.05), breed (introduced Boer mixed breed, p = 0.006) and age (goats ≥3 years old, p = 0.014) were significant risk factors for C. burnetii seropositivity. The results of the survey indicated that province (Vientiane Capital, p<0.001), breed (introduced Boer mixed breed, p<0.001), production system (commercial, p<0.001), age (adult, p = 0.004), and farm size (large, 0.001) were all significant risk factors seropositivity for Brucella spp. It was concluded that Lao goats have been exposed to both C. burnetii and Brucella spp. however the risk of clinical disease has not yet been determined and there is an urgent need to determine human health risks and economic losses caused by Q fever and Brucellosis.